Phosphoric acid doped polybenzimidazole high-temperature proton exchange membrane and preparation method thereof

The phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane prepared by solution in situ composite technology and gradient temperature-raising drying method solves the problems of poor performance and phosphoric acid loss in the existing technology, and achieves high stability and ultra-high proton conductivity.

CN119890375AActive Publication Date: 2025-04-25WUHAN UNIV OF TECH

Patent Information

Application Number
CN202510062058.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Existing high-temperature proton exchange membrane fuel cells have poor performance when operating at high current density, and the loss of phosphoric acid-doped molecules leads to a decrease in stability and proton conductivity.

Method used

Using solution in-situ composite technology, phosphoric acid is directly added to the polybenzimidazole polymer solution, and a high-temperature proton exchange membrane is prepared by gradient heating drying to avoid internal stress and ensure uniform doping of phosphoric acid.

Benefits of technology

A high-temperature proton exchange membrane with high conductivity, high surface conductivity, low hydrogen permeability and excellent mechanical properties is achieved, which significantly improves the stability and proton conductivity of the membrane, and solves the problems of high ohmic polarization and concentration difference polarization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890375A_ABST
    Figure CN119890375A_ABST
Patent Text Reader

Abstract

The invention provides a phosphoric acid doped polybenzimidazole high-temperature proton exchange membrane and a preparation method thereof. In the membrane material, the range of the mass fraction of the phosphoric acid in the polybenzimidazole polymer is greater than 0 wt.% and not greater than 3000 wt.%. The membrane is prepared by the following steps: S1, dissolving a polybenzimidazole polymer in a solvent, and adding phosphoric acid to obtain a composite solution; and S2, casting the composite solution onto a membrane forming container, and drying to obtain the phosphoric acid doped polybenzimidazole high-temperature proton exchange membrane. The phosphoric acid doped polybenzimidazole high-temperature proton exchange membrane not only can be used for preparing HT-PEM without internal stress so as to prevent loss of phosphoric acid, but also can be used for randomly and accurately controlling the phosphoric acid doping amount and thickness of the prepared membrane through the composition and volume of the solution; therefore, the phosphoric acid doped polybenzimidazole composite HT-PEM without internal stress, which has high stability and ultrahigh specific proton conductivity, is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane and a preparation method thereof. Background Art

[0002] The operating temperature of proton exchange membrane fuel cells (PEMFCs) using perfluorosulfonic acid (PFSA)-based ion exchange membranes (PEMs) is limited to below 100 °C due to their strong dependence on high humidity, resulting in complex water-heat management systems and high requirements for fuel purity. Inorganic acid (represented by phosphoric acid)-doped high-temperature resistant aromatic polymers are considered to be the main alternatives for PEMs operating at temperatures above 120 °C under anhydrous conditions, where fuel cells can not only improve CO tolerance but also enhance electrode reaction kinetics and simplify water / heat management of fuel cells. Recently, many studies on inorganic acid-doped polymer membranes have been reported as high-temperature proton exchange membranes (HT-PEMs). In addition, phosphoric acid-doped polybenzimidazole membranes and corresponding membrane electrode assemblies (MEAs) have been successfully commercialized, such as Fumateck AM membranes and Celtec-P series MEAs. However, the performance and durability of high-temperature PEMFCs (HT-PEMFCs) still lag significantly behind those of PFSA-based PEMFCs.

[0003] In addition to the well-known reasons for high activation polarization at low current density due to poisoning of phosphoric acid catalyst and high ohmic polarization at medium current density due to low specific proton conductivity, there is another overlooked factor, that is, the expected high oxygen transport capacity should be achieved by avoiding "flooding", but it is not achieved. In contrast, the reported HT-PEMFC based on phosphoric acid (PA) doped polymer membranes exhibited severe concentration polarization, which was more obvious when operating under back pressure. Therefore, such cells are difficult to operate at high current density and the performance cannot meet the practical application requirements of HT-PEMFCs. In addition, the stability of HT-PEMFC based on phosphoric acid remains problematic due to the continuous loss of doped phosphoric acid molecules from the membrane during fuel cell operation. Although different techniques have been applied to embed acid molecules in the membrane, including polymer modification, introduction of foreign species, and cross-linking of polymer chains, the loss of phosphoric acid molecules can only be improved but not avoided, which inevitably leads to a decrease in the anhydrous proton conductivity of the membrane. The current phosphoric acid doping method is the direct cause of the above problems. The doped phosphoric acid molecules are slowly squeezed out by the internal stress generated in the polymer membrane due to separation from the doping environment. When the membrane is assembled into MEA, this slowly released phosphoric acid enters the catalytic layer and wraps the catalyst, causing gas mass transfer resistance and generating concentration polarization. In addition, the loss of phosphoric acid will increase the internal resistance of the membrane, resulting in greater ohmic polarization.

[0004] Therefore, it is urgent to develop a new method for preparing a polybenzimidazole-based high-temperature proton exchange membrane doped with phosphoric acid, so as to prepare an internal stress-free phosphoric acid-doped polybenzimidazole-based composite HT-PEM with high stability and ultra-high specific proton conductivity. Summary of the invention

[0005] In view of this, the present invention proposes a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane with high electrical conductivity, high surface conductivity, low hydrogen permeation, excellent mechanical properties and ultra-long-term stability and a preparation method thereof.

[0006] In a first aspect, the present invention provides a method for preparing the above-mentioned phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane, comprising the following steps:

[0007] S1, dissolving a polybenzimidazole polymer in a solvent, and adding phosphoric acid to obtain a composite solution;

[0008] S2, casting the composite solution of step S1 onto a membrane-forming container, and drying it to obtain a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane.

[0009] On the basis of the above technical solution, preferably, the polybenzimidazole polymer is an aromatic polymer containing a benzimidazole ring structure.

[0010] More preferably, the polybenzimidazole polymer is selected from at least one of poly(2,5-benzimidazole), poly[2,2′-(m-phenylene)-4,4′-bibenzimidazole], poly[2,2′-(m-phenylene)-5,5′-bibenzimidazole], poly[4,4′-(diphenylene oxide)-5,5′-biphenylene oxide imidazole] or [2,2′-(dihydroxy-1,4-phenylene)-5,5′-bibenzimidazole]. Correspondingly, the polybenzimidazole polymer is selected from at least one of ABPBI, pPBI, mPBI, OPBI or OHPBI.

[0011] On the basis of the above technical solution, preferably, in step S1, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or N-methylpyrrolidone.

[0012] More preferably, the solvent is dimethyl sulfoxide (DMSO).

[0013] By adopting the above technical solution, dimethyl sulfoxide, as an efficient solvent, helps to disperse and dissolve the polymer more evenly during the preparation process, thereby allowing a higher amount of phosphoric acid doping. This not only increases the proton conduction path inside the proton exchange membrane, but also further enhances the proton conductivity, making the final product more conductive under high temperature conditions. In addition, the use of DMSO can also improve the material handling and membrane consistency during the process, ensuring the high quality and stability of the product.

[0014] On the basis of the above technical solution, preferably, in the composite solution, the concentration of the polybenzimidazole polymer solution is 0.1-5wt.%, and the concentration of the phosphoric acid is 65-85wt.%.

[0015] By adopting the above technical solution, it is ensured that the composite solution system can efficiently accommodate a high proportion of phosphoric acid and prevent its precipitation. This specific ratio range allows phosphoric acid to be evenly distributed in the polymer matrix, thereby maximizing proton conductivity without affecting the stability of the solution. The high-temperature proton exchange membrane prepared in this way not only has excellent proton conductivity, but also has good mechanical strength and thermal stability.

[0016] On the basis of the above technical solution, preferably, in step S2, the composite solution of step S1 is cast on a flat glass container and dried to obtain a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane, which specifically includes:

[0017] The composite solution of step S1 was cast onto a membrane-forming container and dried at 100° C. for 24 h, and then dried at 120° C., 140° C. and 160° C. for 2 h each to obtain a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane.

[0018] By adopting the above technical solution, the above high boiling point solvent can be volatilized slowly and evenly, effectively preventing the loss of phosphoric acid during the drying process. Specifically, this gradient temperature drying method not only helps to completely remove the residual solvent, but also ensures the stable doping of phosphoric acid.

[0019] In a second aspect, the present invention provides a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane, wherein the mass fraction of the phosphoric acid in the polybenzimidazole polymer is greater than 0wt.% and not more than 3000wt.%.

[0020] On the basis of the above technical solution, preferably, the phosphoric acid accounts for 1000-2000wt.% of the mass fraction of the polybenzimidazole polymer.

[0021] By adopting the above technical solution, it can be ensured that the high-temperature proton exchange membrane can take into account both mechanical stability and proton conductivity.

[0022] On the basis of the above technical solution, the thickness of the exchange membrane is 5 to 300 μm.

[0023] On the basis of the above technical solution, preferably, the thickness of the exchange membrane is 10 to 100 μm.

[0024] By adopting the above technical solution, within this thickness range, the high-temperature proton exchange membrane can take into account both surface conductivity and gas barrier properties.

[0025] The phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane and the preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art:

[0026] (1) The high-temperature proton exchange membrane and its preparation method provided by the present invention are prepared by directly adding phosphoric acid to a polybenzimidazole polymer solution and then casting it into a membrane, and then drying it by gradient heating. The thickness of the prepared membrane and the phosphoric acid doping content can be accurately controlled to obtain a high-temperature proton exchange membrane with ultra-high proton conductivity, surface conductivity and excellent gas barrier capacity; the solution in-situ doping technology can also avoid the generation of stress in the membrane, thereby preventing the loss of phosphoric acid and greatly improving the stability.

[0027] (2) The phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane of the present invention can not only prepare stress-free HT-PEM to prevent phosphoric acid loss, but also arbitrarily and accurately control the phosphoric acid doping amount and thickness of the prepared membrane through solution composition and volume, so as to prepare stress-free phosphoric acid-doped polybenzimidazole composite HT-PEM with high stability and ultra-high specific proton conductivity. This method effectively solves the major challenges of high ohmic polarization and concentration polarization encountered in HT-PEMFC, and at the same time lays the foundation for reducing catalyst activation polarization caused by phosphoric acid molecule poisoning. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 The H NMR spectrum of poly[4,4′-(diphenyl ether)-5,5′-biphenyl ether imidazole](OPBI) 1 H NMR) spectra;

[0030] Figure 2 This is a cross-sectional scanning electron microscope (SEM) image of the phosphoric acid-doped OPBI (PA / OPBI) high-temperature proton exchange membrane prepared in situ from the solution in Example 1 of the present invention;

[0031] Figure 3 is a stress-strain curve diagram of the PA / OPBI high-temperature proton exchange membrane prepared in Example 1 of the present invention;

[0032] Figure 4 Surface conductivity curves of the PA / OPBI high temperature proton exchange membrane with a thickness of 30 μm and a phosphoric acid doping amount of 1500 wt.% prepared in Example 1 of the present invention at different temperatures;

[0033] Figure 5 The proton conductivity stability of the PA / OPBI high temperature proton exchange membrane with a thickness of 30 μm and a phosphoric acid doping amount of 1500 wt.% prepared in Example 1 of the present invention at 160° C. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] At present, there are two main methods for preparing high-temperature proton exchange membranes: one is the method widely used in academic literature, which is to form a membrane first and then immerse it in a phosphoric acid solution; the other is the method commonly used by manufacturers to directly form a membrane with the reaction solution of synthetic polybenzimidazole (PBI) (using pyrophosphoric acid as solvent) and then hydrolyze it. Although these two traditional methods have their own advantages, they also face some common problems. First, they have significant deficiencies in the control of membrane thickness and phosphoric acid content, making it difficult to achieve precise regulation. Secondly, more seriously, the prepared membrane is prone to phosphoric acid loss during actual application, which not only leads to a rapid decline in material performance, but also affects the long-term stability and reliability of the equipment. The root cause of these problems is that the membranes prepared by the above two methods will inevitably produce strong internal stress, which prompts phosphoric acid molecules to escape from the membrane structure, thereby accelerating the loss of phosphoric acid.

[0036] In view of the fact that the existing technologies are not as good as the inventor's expectations, the inventor made the present invention through further research.

[0037] Based on a deep understanding of the mechanism of phosphoric acid loss, the inventors have proposed a new method for preparing a high-temperature proton exchange membrane without internal stress. By directly using a phosphoric acid-polymer solution to prepare the membrane, this process can not only effectively avoid the generation of internal stress, but also ensure that the phosphoric acid is uniformly and firmly doped in the polymer matrix. Specifically, this method allows for more precise control of the thickness and phosphoric acid content of the membrane, so that the final product performs well in terms of mechanical strength, thermal stability and proton conductivity. In addition, due to the elimination of internal stress, the membrane can significantly reduce the loss of phosphoric acid in practical applications, maintain stable performance and extend service life. Therefore, the present invention provides a more efficient, reliable and easy-to-industrial preparation method, which provides solid technical support for high-performance applications such as high-temperature fuel cells.

[0038] The high temperature proton exchange membrane and the preparation method thereof according to the embodiment of the present invention are described in detail below.

[0039] The present invention provides a method for preparing a solution in-situ composite phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane, which comprises the following steps:

[0040] The polybenzimidazole polymer is dissolved in a solvent, and phosphoric acid is added to the solution;

[0041] The composite solution is cast onto a membrane-forming container, such as a flat glass container or a container made of polytetrafluoroethylene, and dried to obtain the high-temperature proton exchange membrane.

[0042] The polybenzimidazole polymer in the present invention is selected from aromatic polymers containing a benzimidazole ring structure, such as poly(2,5-benzimidazole), poly[2,2′-(m-phenylene)-4,4′-bibenzimidazole], poly[2,2′-(m-phenylene)-5,5′-bibenzimidazole], poly[4,4′-(diphenylene ether)-5,5′-biphenylene ether imidazole] or [2,2′-(dihydroxy-1,4-phenylene)-5,5′-bibenzimidazole].

[0043] The solvent in the present invention is any one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, and the concentration of the polybenzimidazole polymer solution is 0.1-5wt.%. Preferably, in a preferred embodiment of the present invention, the solvent is dimethyl sulfoxide, and the obtained composite membrane can be doped with more phosphoric acid and has a higher proton conductivity. Preferably, the solution concentration is 0.1, 0.5, 1, 3, 5wt.%, etc., and the polymer solution system of this concentration can further incorporate phosphoric acid.

[0044] The phosphoric acid concentration in the present invention is 65-85wt.%. Preferably, the phosphoric acid concentration is 65, 70, 75, 80 or 85wt.%, etc., and this phosphoric acid concentration can ensure that the polymer does not precipitate from the solution. The mass fraction of the phosphoric acid relative to the polybenzimidazole polymer is 0-3000wt.%, and the preferred mass fraction is 1000-2000wt.%. This mass fraction can ensure that the obtained membrane can take into account both mechanical stability and proton conductivity.

[0045] In the present invention, drying is first performed at 100°C for 24 hours, so that the high boiling point solvent can evaporate slowly, ensuring that the phosphoric acid in the film is not lost during the drying process. Then, drying is performed at 120°C, 140°C and 160°C for 2 hours respectively, ensuring that the phosphoric acid is not lost during the drying process and completely removing the solvent.

[0046] The thickness of the solution in-situ composite phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane prepared in the present invention is 5-300 μm. Preferably, the thickness is 10-100 μm. Within this thickness range, the high-temperature proton exchange membrane can take into account both surface conductivity and gas barrier properties. The thickness of the composite proton exchange membrane can be, for example, 10 μm, 40 μm, 70 μm or 100 μm, etc., and the staff in this field can set it within this range according to actual needs.

[0047] The features and properties of the present invention are further described in detail below in conjunction with the examples. If no specific conditions are specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0048] The phosphoric acid-doped polybenzimidazole high-temperature proton exchange membranes prepared in the following examples and comparative examples were subjected to the following performance tests, including:

[0049] (1) Proton conductivity and surface conductivity test

[0050] The frequency response analyzer is used for testing, and the frequency sweep range is 1-10 6 Hz, the AC signal amplitude is 50mV. The membrane materials prepared in each embodiment and comparative example were cut into a size of length × width = 2.5cm × 1cm, and tested by two-electrode AC impedance method. Before the test, the membrane samples were placed at a test temperature of 160°C for 0.5 hours. The proton conductivity σ (mS / cm) and surface conductivity (SPC, S / cm -2 ) is calculated by the following formula:

[0051]

[0052] SPC = σ / d;

[0053] Where L and A are the distance between the two electrodes and the effective cross-sectional area of ​​the film to be measured between the two electrodes, respectively; R is the resistance of the film, which is obtained by the Nyquist plot obtained by AC impedance testing; and d is the thickness of the film.

[0054] (2) Tensile strength and elongation at break test

[0055] The film was cut into rectangular strips with a length of 80 mm and a width of 10 mm, and tested on an electronic tensile machine at a tensile speed of 1 mm / min. The temperature and humidity were 25° C. and 50% RH, respectively.

[0056] (3) Hydrogen permeation current density

[0057] Linear sweep voltammetry (LSV) was used to test the hydrogen permeation current density of the membrane electrode to characterize the gas barrier properties of the PEM. Before the test, nitrogen was passed through both sides of the electrode to purge the cell voltage to below 0.1 V. During the test, 200 mL min was input to the anode and cathode respectively. -1 H2 and nitrogen at 30℃ and no back pressure at 2mV·s -1 The scan rate was scanned from 0.1V to 0.7V. In this experiment, the hydrogen permeation current density (j H2@0.4V ) size characterizes the hydrogen permeability of the membrane.

[0058] Example 1

[0059] The phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane of this embodiment is obtained by the following steps:

[0060] (1) 0.1 g of OPBI was dissolved in 20 g of dimethyl sulfoxide at 100° C. to form a 0.5 wt.% solution; then 1.76 g of a phosphoric acid solution with a mass concentration of 85% was added dropwise to the solution system and stirred for 1 hour to obtain a composite solution;

[0061] (2) The composite solution in step 1 is cast onto a flat glass container, dried at 100° C. for 24 hours, and then dried at 120° C., 140° C., and 160° C. for 2 hours, respectively, to obtain a phosphoric acid-doped OPBI (PA / OPBI) high-temperature proton exchange membrane having a phosphoric acid doping content of 1500 wt.% and a thickness of 30 μm.

[0062] The above performance test was performed on the proton exchange membrane prepared in this example, and the performance test results shown in Table 1 were obtained.

[0063] Table 1 Performance test results

[0064] Performance Indicators Test Results Proton conductivity (mS / cm, 160℃) 366 <![CDATA[Surface conductivity (S / cm 2 , 160 °C)]]> 122.1 Tensile strength(MPa) 3.8 Elongation at break (%) 362 <![CDATA[Hydrogen permeation current density (mA·cm -2 )]]> 0.45

[0065] Comparative Example 1

[0066] In this comparative example, a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane was prepared by a traditional membrane preparation strategy. The specific preparation steps are as follows, and the performance test results are shown in Table 2:

[0067] (1) 0.3 g of OPBI was dissolved in dimethyl sulfoxide at 100° C. to form a 1 wt.% solution. The solution was then cast onto a flat glass container and dried at 100° C. for 24 hours and then at 160° C. for 2 hours.

[0068] (2) The OPBI membrane in step (1) was immersed in 85 wt.% phosphoric acid at 160° C. for 2 hours, the membrane was taken out and the phosphoric acid on the surface was wiped off to obtain a phosphoric acid-doped OPBI (PA / OPBI) high-temperature proton exchange membrane with a phosphoric acid doping content of 620 wt.% and a thickness of 95 μm.

[0069] Table 2 Performance test results

[0070] Performance Indicators Test Results Proton conductivity (mS / cm, 160℃) 133 <![CDATA[Surface conductivity (S / cm 2 , 160 °C)]]> 14 Tensile strength(MPa) 9 Elongation at break (%) 182 <![CDATA[Hydrogen permeation current density (mA·cm -2 )]]> 2.1

[0071] Combining the performance test results in Tables 1 and 2, it can be seen that the proton conductivity, surface conductivity and toughness of the PA / OPBI high-temperature proton exchange membrane prepared by in-situ solution compounding in Example 1 are higher than those of the PA / OPBI high-temperature proton exchange membrane prepared by traditional membrane preparation strategies. At the same time, the gas barrier property of the membrane is also significantly better than that of the traditional membrane, which can meet the use requirements of high-temperature proton exchange membrane fuel cells.

[0072] In addition, from Figure 1 The H NMR spectrum can confirm that the polymer used is OPBI structure; Figure 2 It can be seen that the prepared PA / OPBI film is relatively flat and has no defects such as cracks; Figure 3 It was confirmed that the tensile strength of the prepared membrane was 3.8MPa, which can meet the application requirements of fuel cells; Figure 4 This indicates that the proton surface conductivity of the prepared membrane can reach 122.1S / cm 2 ; Figure 5 It shows that the proton conductivity of the prepared PA / OPBI membrane does not decrease significantly within 1200 hours at 160°C.

[0073] Example 2

[0074] The phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane of this embodiment is obtained by the following steps:

[0075] (1) 0.1 g of pPBI was dissolved in 20 g of N-methylpyrrolidone at 100° C. to form a 0.5 wt.% solution; then 1.76 g of a phosphoric acid solution with a mass concentration of 85% was added dropwise to the above system and stirred for 1 hour to obtain a composite solution;

[0076] (2) The composite solution in step 1 is cast onto a flat glass container, dried at 100° C. for 24 hours, and then dried at 120° C., 140° C. and 160° C. for 2 hours respectively to obtain a phosphoric acid-doped pPBI (PA / pPBI) high-temperature proton exchange membrane with a phosphoric acid doping content of 500 wt.% and a thickness of 100 μm.

[0077] The performance test results are shown in Table 3.

[0078] Table 3 Performance test results

[0079] Performance Indicators Test Results Proton conductivity (mS / cm, 160℃) 78 <![CDATA[Surface conductivity (S / cm 2 , 160 °C)]]> 7.8 Tensile strength(MPa) 8.3 Elongation at break (%) 147 <![CDATA[Hydrogen permeation current density (mA·cm -2 )]]> 0.12

[0080] Comparative Example 2

[0081] The difference from Example 2 is that in step (1), 0.1 g of pPBI is dissolved in N-methylpyrrolidone at 100° C. to form a 0.08 wt. % solution, and the other steps remain unchanged. The performance test results are shown in Table 4.

[0082] Table 4 Performance test results

[0083] Performance Indicators Test Results Proton conductivity (mS / cm, 160℃) 65 <![CDATA[Surface conductivity (S / cm 2 , 160 °C)]]> 6.5 Tensile strength(MPa) 7.9 Elongation at break (%) 135 <![CDATA[Hydrogen permeation current density (mA·cm -2 )]]> 0.14

[0084] Comparative Example 3

[0085] The difference from Example 2 is that in step (1), 0.1 g of pPBI is dissolved in N-methylpyrrolidone at 100° C. to form a 5.5 wt. % solution, and the other steps remain unchanged. The performance test results are shown in Table 5.

[0086] Table 5 Performance test results

[0087]

[0088]

[0089] By comparing the performance test results of Example 2 and Comparative Examples 2 to 3, it can be seen that in Comparative Example 2, due to the low polymer concentration, the phosphoric acid doping amount is relatively high, but the membrane structure may not be dense enough, so the proton conductivity and surface conductivity are slightly reduced. In Comparative Example 3, due to the high polymer concentration, the membrane structure is more dense, but the phosphoric acid doping amount is relatively reduced, so the proton conductivity and surface conductivity are slightly low.

[0090] Example 3

[0091] The phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane of this embodiment is obtained by the following steps:

[0092] (1) 0.1 g of OPBI was dissolved in 100 g of dimethyl sulfoxide at 100° C. to form a 0.1 wt.% solution; then 1.76 g of a phosphoric acid solution with a mass concentration of 85% was added dropwise to the solution system and stirred for 1 hour to obtain a composite solution;

[0093] (2) The composite solution in step 1 is cast onto a flat glass container, dried at 100° C. for 24 hours, and then dried at 120° C., 140° C., and 160° C. for 2 hours, respectively, to obtain a phosphoric acid-doped OPBI (PA / OPBI) high-temperature proton exchange membrane having a phosphoric acid doping content of 1000 wt.% and a thickness of 10 μm.

[0094] The performance test results are shown in Table 6.

[0095] Table 6 Performance test results

[0096] Performance Indicators Test Results Proton conductivity (mS / cm, 160℃) 162 <![CDATA[Surface conductivity (S / cm 2 , 160 °C)]]> 81 Tensile strength(MPa) 2.8 Elongation at break (%) 236 <![CDATA[Hydrogen permeation current density (mA·cm -2 )]]> 0.50

[0097] Comparative Example 4

[0098] The difference from Example 3 is that in step (2), the composite solution in step 1 is cast onto a flat glass container and dried at 100°C for 30 hours to obtain a phosphoric acid-doped OPBI (PA / OPBI) high-temperature proton exchange membrane with a phosphoric acid doping content of 1000wt.% and a thickness of 10μm.

[0099] The performance test results are shown in Table 7.

[0100] Table 7 Performance test results

[0101] Performance Indicators Test Results Proton conductivity (mS / cm, 160℃) 158 <![CDATA[Surface conductivity (S / cm 2 , 160 °C)]]> 79 Tensile strength(MPa) 1.2 Elongation at break (%) 107 <![CDATA[Hydrogen permeation current density (mA·cm -2 )]]> 1.25

[0102] By comparing Example 3 and Comparative Example 4, we can see that if the gradient temperature increase drying method is not adopted, the cross-linking and entanglement of the polymer during the film formation process will be weak, thereby reducing its mechanical strength and increasing the hydrogen permeability.

[0103] Example 4

[0104] The phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane of this embodiment is obtained by the following steps:

[0105] (1) 0.1 g of OPBI was dissolved in 1.9 g of dimethyl sulfoxide at 100° C. to form a 5 wt.% solution; then 1.76 g of phosphoric acid was added dropwise to the solution system and stirred for 1 hour to obtain a composite solution;

[0106] (2) The composite solution in step 1 is cast onto a flat glass container, dried at 100° C. for 24 hours, and then dried at 120° C., 140° C. and 160° C. for 2 hours respectively to obtain a phosphoric acid-doped OPBI (PA / OPBI) high-temperature proton exchange membrane with a phosphoric acid doping content of 2000 wt.% and a thickness of 50 μm.

[0107] The performance test results are shown in Table 8.

[0108] Table 8 Performance test results

[0109]

[0110]

[0111] Example 5

[0112] The difference from Example 4 is that the phosphoric acid doping content is 3000 wt.%, and the phosphoric acid doped OPBI (PA / OPBI) high temperature proton exchange membrane has a thickness of 5 μm.

[0113] The performance test results are shown in Table 9.

[0114] Table 9 Performance test results

[0115] Performance Indicators Test Results Proton conductivity (mS / cm, 160℃) 289 <![CDATA[Surface conductivity (S / cm 2 , 160 °C)]]> 578 Tensile strength(MPa) 0.7 Elongation at break (%) 143 <![CDATA[Hydrogen permeation current density (mA·cm -2 )]]> 1.87

[0116] By comparing Example 1 with Examples 3 to 5, it can be seen that when the phosphoric acid doping content is 1000 to 2000 wt.%, and the membrane thickness is 10 to 100 μm, the mechanical properties of the membrane can meet the requirements of fuel cell assembly, and the hydrogen permeability is also low. Although the thinner membrane has extremely high proton conductivity, its mechanical strength is low and it is difficult to be used in practice.

[0117] The inventors obtained the following Examples 6 to 10 by replacing the solvent in Example 1, as shown in Table 10, and recorded the performance test results in the following Table 11.

[0118] Table 10 Solvent types

[0119]

[0120] Table 11 Performance test results

[0121]

[0122] By comparing the above Examples 6 to 10 and Example 1, it can be seen that the solvent is dimethyl sulfoxide, the obtained composite membrane can be doped with more phosphoric acid and has a higher proton conductivity. Due to the similar membrane thickness, the mechanical properties and hydrogen permeation current are slightly different.

[0123] Comparative Example 5

[0124] The difference from Example 5 is that commercial polyphenylene ether with a number average molecular weight of 67 kDa is used instead of polybenzimidazole as a comparison. The performance test results are shown in Table 12.

[0125] Table 12 Performance test results

[0126] Performance Indicators Test Results Proton conductivity (mS / cm, 160℃) 172 <![CDATA[Surface conductivity (S / cm 2 , 160 °C)]]> 344 Tensile strength(MPa) 0.67 Elongation at break (%) 129 <![CDATA[Hydrogen permeation current density (mA·cm -2 )]]> 1.02

[0127] It can be seen from Table 12 that aromatic polymers containing benzimidazole ring structures exhibit better comprehensive properties.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane, characterized in that: The steps include: S1, dissolving a polybenzimidazole polymer in a solvent, and adding phosphoric acid to obtain a composite solution; S2, casting the composite solution of step S1 onto a membrane-forming container, and drying it to obtain a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane.

2. The method for preparing a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane according to claim 1, characterized in that: The polybenzimidazole polymer is an aromatic polymer containing a benzimidazole ring structure.

3. The method for preparing a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane according to claim 2, characterized in that: The polybenzimidazole polymer is selected from at least one of poly(2,5-benzimidazole), poly[2,2′-(m-phenylene)-4,4′-bibenzimidazole], poly[2,2′-(m-phenylene)-5,5′-bibenzimidazole], poly[4,4′-(diphenylene ether)-5,5′-biphenylene ether imidazole] or [2,2′-(dihydroxy-1,4-phenylene)-5,5′-bibenzimidazole].

4. The method for preparing a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane according to claim 1, characterized in that: In step S1, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or N-methylpyrrolidone.

5. The method for preparing a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane according to claim 4, characterized in that: In the composite solution, the concentration of the polybenzimidazole polymer solution is 0.1-5wt.%, and the concentration of phosphoric acid is 65-85wt.%.

6. The method for preparing a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane according to claim 1, characterized in that: Step S2 specifically includes: The composite solution of step S1 was cast onto a flat glass container and dried at 100° C. for 24 h, and then dried at 120° C., 140° C. and 160° C. for 2 h each to obtain a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane.

7. A phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The mass fraction of the phosphoric acid in the polybenzimidazole polymer is in the range of greater than 0 wt. % and not more than 3000 wt. %.

8. The phosphoric acid-doped polybenzimidazole high temperature proton exchange membrane according to claim 7, characterized in that: The phosphoric acid accounts for 1000-2000 wt.% of the mass fraction of the polybenzimidazole polymer.

9. The phosphoric acid-doped polybenzimidazole high temperature proton exchange membrane according to claim 7, characterized in that: The thickness of the exchange membrane is 5 to 300 μm.

10. The phosphoric acid-doped polybenzimidazole high temperature proton exchange membrane according to claim 9, characterized in that: The thickness of the exchange membrane is 10-100 μm.

Citation Information

Patent Citations

  • Method for preparing phosphate doped polybenzimidazoles membrane by employing polybenzimidazoles- phosphoric acid- water ternary system

    CN101157763A

  • Preparation method of phosphoric acid doped polybenzimidazole cross-linked membrane

    CN111342098A

  • Preparation method of membrane electrode of high-temperature polymer electrolyte membrane fuel cell

    CN114628751A

  • Polymer electrolyte membrane based on phosphoric acid doped quaternized polyphenyl ether crosslinked polybenzimidazole and preparation method thereof

    CN117133954A

  • Double-wide-range and high-acid-retention gel state mixed matrix PBI proton exchange membrane as well as preparation method and application thereof

    CN118919787A

Cited By

  • Composite proton exchange membrane and preparation method thereof

    CN120453429A

  • A composite proton exchange membrane and its preparation method

    CN120453429B

  • In-situ reduced MnO2 doped high-temperature proton exchange composite membrane, and preparation method and application thereof

    CN122659208A